Countering Violent Extremism in Tunisia – Between Dependency and Self-Reliance - Lydia Letsch (Journal for Deradicalization, 2018)
In current counter-terrorism efforts, the potential of civil society organizations is recognized by international actors for countering radical narratives and implementing prevention activities in non-Western countries. Civil society-led interventions, it is assumed, constitute a more sustainable as well as locally acceptable approach to reduce the threat of radicalization. In line with this, international actors including EU, UN and EU key-member states have lately incorporated this strategy in Tunisia, which since the fall of the Ben Ali regime in 2011 has experienced an increase in jihadist activities challenging the democratic consolidation of the country. In response to growing donor interest, the bulk of civil society organizations in Tunisia have recently started to develop policies and programs to counter violent extremism and radicalization. However, the lack of comprehensive empirical research on civil society engagement in counter- as well as de-radicalization complicates the assessment of scope and impact of these initiatives on local communities in Tunisia. To encounter this lacuna, this paper focuses on the experiences, subjective perception and practices of activists working on the ground in an arising Tunisian Countering Violent Extremism (CVE) landscape. (Critical) peacebuilding and development literature on civil society is introduced to investigate the interplay of international and local actors in the context of CVE interventions. 25 in-depth narrative interviews with local activists and international experts involved in developing CVE initiatives in Tunisia root this paper in rich empirical data that was analyzed by applying a Grounded Theory methodology. Due to the high dependency of civil society actors on external funding, international actors exert a strong influence on how preventative activities are designed and implemented and which local actors are involved. This paper further shows that this dependency does not just result in agenda adaptation, but rather that local actors, to some extent, can resist to the imposed donor agenda or strategically use the increased donor attention for their own purpose.